Study Of Productivity And Costs On The Implementation Method Of Foundation Work Using Precast Concrete Pile As A Substitute To The Use Of Wooden Pile Foundations In Low Rise Building (Housing) - Syahrudin, Syahrudin; Safaruddin, Nuh M.; S, Soeryamassoeka B; Erwin, Sutandar (Fakultas Teknik Universitas Tanjungpura, 2022)
The soil condition in Pontianak City is mostly soft soil and peat soil which causes the low bearing capacity of the soil. Various efforts have been made to increase the bearing capacity of the soil, such as the use of wooden pile (kayu cerucuk). With the limited availability of wooden pile, the use of precast piles is an alternative in increasing the bearing capacity of the soil on the foundations of buildings/housings in Pontianak City. The purpose of this study is to compare the productivity and costs of using a wooden pile foundation measuring 12/15 cm with a length of 9-12 M against the use of a square precast concrete pile foundation measuring 15x15 cm2 with a segment length of 3-4 M at a depth of 12-20 M and a size of 12-20 M. 20x20 cm2 with a segment length of 6 M at a depth of 12-18 M in low-rise buildings in Pontianak City. From the results of the study, it is known that the productivity and average cost of piling per M' in a 2-storey shophouse building with an alternative foundation using 12/15 cm cerucuk piles is 22.3 seconds/m' at a cost of Rp. 17,306.24, precast piles square 15 x 15 cm2 of 111.5 seconds/m' at a cost of Rp. 144,274,439 and precast square piles of 20 x 20 cm2 of 125.7 seconds/m' at a cost of Rp. 291,338,955. In a type 150 house building with an alternative foundation using 12/15 cm wooden piles of 18.05 seconds/m' at a cost of Rp. 17,185.58, precast square piles of 15 x 15 cm2 of 104.67 seconds/m at a cost of Rp. 143,890.04 and 20 x 20 cm2 square precast piles of 94.66 seconds/m' with a cost of Rp. 289,724.234. The cost of foundation work with alternative foundations using precast square piles of 15 x 15 cm2 is the most efficient both from the aspect of driving costs, overall costs and the cost of the unit load carried by the foundation